Effect of Supplementation of Monensin Sodium on rumen metabolism and Milk Yield in Early Lactating Buffalo (Bubalus Bubalus) - viraj, Prath (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
The study was carried out to assess the effect of monensin sodium supplementation on rumen fermentation metabolites and milk yield in early lactating buffaloes. Twelve buffaloes in their 2nd week of lactation were selected. Control group was fed on standard ration whereas the treatment group was supplemented with monensin sodium @ 200 mg/head/day in addition to standard ration. Rumen liquor and blood sample was collected at 2nd and 12th week of lactation. Total and individual volatile fatty acids concentration was estimated by gas chromatography. Monensin sodium (P
Keywords: TVFA; Acetate/Propionate ratio; buffalo; Monensin sodium